2002
DOI: 10.1071/aj01016
|View full text |Cite
|
Sign up to set email alerts
|

Carnarvon Basin Architecture and Structure Defined by the Integration of Mineral and Petroleum Exploration Tools and Techniques

Abstract: The Barrow and Dampier Sub-basins of the Northern Carnarvon Basin developed by repeated reactivation of long-lived basement structures during Palaeozoic and Mesozoic tectonism. Inherited basement fabric specific to the terranes and mobile belts in the region comprise northwest, northeast, and north–south-trending Archaean and Proterozoic structures. Reactivation of these structures controlled the shape of the sub-basin depocentres and basement topography, and determined the orientation and style of structures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Our study area is located within the Exmouth Plateau, a region of the North Carnarvon Basin containing <10 km thick, stretched continental crust and an up to 18 km thick sedimentary sequence (Figure 1) [e.g. Exon et al 1992;Karner and Driscoll 1999;Pryer et al 2002;Stagg et al 2004]. To the north and west of the Exmouth Plateau are the Argo and Gascoyne abyssal plains, respectively, which consist of oceanic crust; between the Exmouth Plateau and the Gascoyne Abyssal Plain is a 200-250 km wide continent-ocean transition zone comprising heavily intruded continental crust ( Figure 1A) [e.g.…”
Section: Geological Settingmentioning
confidence: 99%
“…Our study area is located within the Exmouth Plateau, a region of the North Carnarvon Basin containing <10 km thick, stretched continental crust and an up to 18 km thick sedimentary sequence (Figure 1) [e.g. Exon et al 1992;Karner and Driscoll 1999;Pryer et al 2002;Stagg et al 2004]. To the north and west of the Exmouth Plateau are the Argo and Gascoyne abyssal plains, respectively, which consist of oceanic crust; between the Exmouth Plateau and the Gascoyne Abyssal Plain is a 200-250 km wide continent-ocean transition zone comprising heavily intruded continental crust ( Figure 1A) [e.g.…”
Section: Geological Settingmentioning
confidence: 99%
“…Since the Early Cretaceous, the dominant tectonic control has been thermal subsidence (Veevers et al ., ; Baillie et al ., ; Driscoll & Karner, ; Cathro & Karner, ). Several studies have suggested an interruption of such subsidence because of collision between the Banda Arc and Australia, which began in the late Miocene (Veevers et al ., ; Baillie et al ., ; Lee & Lawver, ; Driscoll & Karner, ; Hull & Griffiths, ; Pryer et al ., ; Cathro & Karner, ). However, the impact of this collision on the NCB has been limited to localized uplift (only up to 75 m) at the northwest end of the Rosemary–Legendre structural trend during the Miocene, inferred from seismic stratigraphy integrated with kinematic and flexural modelling in the adjacent Dampier sub‐basin (Figs a and ; Cathro & Karner, ).…”
Section: Geological Setting: Northern Carnarvon Basin Northwest Shelmentioning
confidence: 97%
“…The locations of other figures shown in this paper are indicated by bold numbers. which began in the late Miocene (Veevers et al, 1991;Baillie et al, 1994;Lee & Lawver, 1995;Driscoll & Karner, 1998;Hull & Griffiths, 2002;Pryer et al, 2002;Cathro & Karner, 2006). However, the impact of this collision on the NCB has been limited to localized uplift (only up to 75 m) at the northwest end of the Rosemary-Legendre structural trend during the Miocene, inferred from seismic stratigraphy integrated with kinematic and flexural modelling in the adjacent Dampier sub-basin (Figs 1a and 2; Cathro & Karner, 2006).…”
Section: Geological Setting: Northern Carnarvon Basin Northwest Shelmentioning
confidence: 99%
“…Our study area is located within the Exmouth Plateau, a region of the North Carnarvon Basin containing <10 km thick, stretched continental crust and an up to 18 km thick sedimentary sequence (Fig. 1) [e.g., Exon et al, 1992;Karner and Driscoll, 1999;Pryer et al, 2002;Stagg et al, 2004]. To the north and west of the Exmouth Plateau are the Argo and Gascoyne abyssal plains, respectively, which consist of oceanic crust; between the Exmouth Plateau and the Gascoyne Abyssal Plain is a 200-250 km wide continent-ocean transition zone 5 comprising heavily intruded continental crust (Fig.…”
Section: Geological Settingmentioning
confidence: 99%